Analisis Implementasi Digitalisasi Kualitas Pelayanan Publik - Aidi, Ahmadi; Budiwaluyo, Agus; Agoestyowati, Redjeki; Ahmad Junaidi, Ahmad Junaidi; Usman, Usman (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
The topic to be analysed in this paper is the digitalisation of public service quality, which is an effort to improve public services using digital technology and data. Digitalisation of public service quality focuses on providing services that are more efficient effective and more transparent. Digitalisation of public service quality is implemented in the transformation of technology from analogue to digital processes. This topic is interesting to study because it is motivated by the results of Cordella &; Lindgren et al, 2019; Ranerup & Henriksen, 2019; Wihlborg, Wirtz et al, 2019), the conclusion of their research is